FUNCTIONAL ANALYSIS OF TEXTS IN ENGLISH AND UZBEKI - Rasulova Nigina Alisherovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article analyzes the features of the functional styles of English and Uzbek languages, the complexity of understanding texts in different styles.